2015
DOI: 10.1080/10255842.2015.1043906
|View full text |Cite
|
Sign up to set email alerts
|

Intervertebral reaction force prediction using an enhanced assembly of OpenSim models

Abstract: OpenSim offers a valuable approach to investigating otherwise difficult to assess yet important biomechanical parameters such as joint reaction forces. Although the range of available models in the public repository is continually increasing, there currently exists no OpenSim model for the computation of intervertebral joint reactions during flexion and lifting tasks. The current work combines and improves elements of existing models to develop an enhanced model of the upper body and lumbar spine. Models of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 46 publications
0
51
0
1
Order By: Relevance
“…For the range of motions (ROM) investigated in the present study, the predictive performance of the base model for normalized and absolute compressive joint forces was within an accuracy of 10% compared to reported in vivo intradiscal pressure measurements and biomechanical model predictions. The force development during simulated dynamic movement (forward–backward flexion) could furthermore be predicted with good agreement to measured in vivo implant loads …”
Section: Methodsmentioning
confidence: 71%
See 1 more Smart Citation
“…For the range of motions (ROM) investigated in the present study, the predictive performance of the base model for normalized and absolute compressive joint forces was within an accuracy of 10% compared to reported in vivo intradiscal pressure measurements and biomechanical model predictions. The force development during simulated dynamic movement (forward–backward flexion) could furthermore be predicted with good agreement to measured in vivo implant loads …”
Section: Methodsmentioning
confidence: 71%
“…Bushing elements placed in each joint mimic overall rotational joint stiffnesses as expected from passive elements such as discs and ligaments. The calibration of bushing and details about joint implementation can be found in a separate publication on the musculoskeletal model …”
Section: Methodsmentioning
confidence: 99%
“…Further modelling developments will include the replacement of neck kinematic constraints with contact models [28, 83] and the inclusion of EMG driven simulations [84] for the estimation of muscle forces. Future application of the models will firstly include the simulation of injurious events, and the analysis of neck muscle contribution to cervical spine loading during rugby activities, such as scrummaging and tackling.…”
Section: Discussionmentioning
confidence: 99%
“…If true, this would further imply that, deploying a pelvic restraint, as done by Harada et al and others (Okawa et al, 1998;Teyhen et al, 2007;Wu et al, 2014), might not significantly alter lumbar motion profiles, although it obviously precludes an accounting of the pelvic contribution, which, as Tafazzol et al have shown, can be significant. The flexed spine also experiences the largest compressive forces compared to other postures (Anderson et al, 1986;Han et al, 2012;Schultz et al, 1982;Senteler et al, 2015;Tafazzol et al, 2014;Wilke et al, 1999). Overloading has particularly been shown to be a prominent biomechanical risk factor for L5-S1 disk disorders (Waters et al, 1993).…”
Section: Mean 95% CImentioning
confidence: 98%
“…In both cases, an accurate description of dynamic, threedimensional (3D) vertebral kinematics is necessary (Waters et al, 1993). This is because (a) normal functional motion benchmarks are mainly based on kinematic measures, and (b) given the infeasibility of direct measurement, in vivo forces experienced by lumbar tissue structures are estimated from biomechanical models (Cholewicki et al, 1991;de Zee et al, 2007;Han et al, 2012;Senteler et al, 2015;Stokes and Gardner-Morse, 1995;Waters et al, 1993;Zhu et al, 2013), the process of which is highly sensitive to the quality of kinematic input.…”
Section: Introductionmentioning
confidence: 99%